Control system design and transient analysis of a grid integrated wind turbine - Shaon Ahmed (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2014)
In this thesis, a new maximum power point tracking algorithm for wind energy conversion systems has been proposed to get rid of these problems. The algorithm is based on the optimum relationship between active power and dc link voltage. The dc power is calculated from voltage and current, which are read by the algorithm.